Ethnomathematics and Ethnography, an anthropological possibility - Jean-Pierre, Decillon; Pinho, Edrisse José Azevedo; Martins, Igor Micheletto (Educação Matemática Debate, 2024)
The discussion in this essay highlights the ethnographic approach and its relevance in ethnomathematical research, emphasizing its importance for understanding traditional mathematical knowledge. The concepts of becoming a sorcerer, becoming a mandira and becoming a child, illustrate the dynamic transformation of the researcher in contact with cultural realities permeated by beliefs and myths. These notions show that the relationship between researchers and communities is not limited to observation, but requires a deep immersion that enables the co-construction of knowledge and a broader understanding of cultural identities. These perspectives also contribute to a more inclusive Mathematics Education, valuing the diversity of knowledge and experiences.